Political ecologies of value: Austerity and socio-environmental conflict in the Italian South - Pusceddu, A.M. (2022)
In Italy, the lack of massive mobilisations against austerity politics can explain the re-awakening of environmental conflicts as catalysers of social discontent. This chapter explores how austerity intensified already existing environmental conflicts, and how this helped to recast the environmental question in ways through which the intersection of multiple experiences of dispossession was comprehensively understood. I develop the notion of political ecologies of value to illuminate working people’s lived experiences and their reactions to persistent socio-environmental disenfranchisement and devaluation particularly in times of crisis and austerity. Drawing on a single case study, an industrial city in southern Italy, I address the revaluation projects underpinning the conflict around socio-ecological arrangements that are considered unfair, unsustainable and detrimental to life. In the context of the austerity crisis, the environmental question provided the basis for building a politics of articulation between different stances and sectors of society, thus voicing multiple experiences of dispossession in the face of a longstanding history of environmental degradation and lasting socio-economic crisis.